PREVALENCE OF HELICOBACTER PYLORI INFECTION IN CHILDREN WITH GASTRODUODENAL PATHOLOGY - N.H. Khudayberganova; G.K. Rakhmatullaeva (Western European Studies, 2023)
Despite the presence of studies devoted to the study of the bacterium Helicobacter pylori, its role in the pathogenesis of diseases such as chronic gastritis, gastric and duodenal ulcers, MALT lymphoma and gastric adenocarcinoma, the question of what determines the development of one or another clinical form of gastroduodenal pathology remains open. One of the factors with which the characteristics of clinical forms of Helicobacter pylori-associated diseases are usually associated is the genetic characteristics of the microorganism, which determines its virulence.
Keywords: chronic gastritis; peptic ulcer of the stomach and duodenum; Helicobacter pylori